Tectonics and sedimentation of a late proterozoic Damaran convergent continental margin, Khomas Hochland, central Namibia. - Kukla, Peter Alfred. (My University, 1990)
The Late Proterozoic Damara Oroqen (750-450 Ma} in Namibia forms part of the Pan-African mobile belt system which dissects southern Africa. The Khomas Trough in the inland branch of the orogen comprises thick multiply deformed metagraywackes and pelites of the Kuisab Formation. (Abbreviation abstract).
A Dissertation submitted to the Faculty of science, University of the Witwatersrand, Johannesburg, for the Degree of Doctor of Philosophy
Keywords: Geology, Structural -- Research -- Namibia.; Sedimentation and deposition -- Research -- Namibia.